Genetics of resistance to endoparasites and ectoparasites - Baker, R.L. (1999)
There was considerable interest and discussion related to the progress made in both the Australian and New Zealand breeding schemes that assist commercial ram breeders to incorporate selection for resistance to gastrointestinal nematode parasites into their breeding programmes along with selection for the usual production traits. The opinion was expressed that assessment of resistance to gastrointestinal nematode parasites should be based on an artificial infection with a known larval challenge rather than by natural pasture challenge as is being commonly utilised in Australia and New Zealand. Research in these places has also shown that there is a very high genetic correlation between artificial challenge and natural pasture challenge. The use of faecal egg counts in sheep and goats as the most important currently available selection criteria for resistance was also strongly supported. A 3 year experiment in Armidale which was recently conducted helped quantify the relative importance of different strategies for the control of gastrointestinal nematode parasites. The effects of nutrition, vaccination and strategic drenching on lines of Merino sheep that were resistant and susceptible to H. contortus were investigated. Papers by Stear, Grumer and Frisch on this issue are reviewed here.